Feeding behavior of sheep in feedlot and fed with diets containing detoxified castor cake in substitution to the soybean meal - Pompeu, Roberto Cláudio Fernandes Franco; Rogério, Marcos Cláudio Pinheiro; Cândido, Magno José Duarte; Bomfim, Marco Aurelio Delmondes; Pereira, Elzânia Sales; Lopes, Marcos Neves; Araújo, Ricardo Alves de (Acta Scientiarum. Animal Sciences, 2022)
To evaluate the ingestive behavior of sheep confined and fed with substitution levels of soybean meal (SM) by detoxified castor cake (DCC). We adopted a completely randomized design, with four levels of substitution (0; 33; 67 and 100%) with five replicates (sheep). We estimated the percentages of total times of intake of feed, time of rumination, in ‘other activities’, in idle agreed and in idle sleeping, dividing the day into eight periods (5h00 to 8h00; 8h01 to 11h00; 11h01 to 14h00; 14h01 to 17h00; 17h01 to 20h00; 20h01 to 23h00; 23h01 to 2h00 and 2h01 to 5h00). No interaction was observed between levels of substitution of the SM by DCC and period of the day to go. However, the isolated effect period of the day, there is more time to go from 8h00 to 11h00. The time rumination was not influenced by the levels of substitution of the SM by DCC. As for the variable other activities, the level of 67% DCC was superior to that of 100%. Regarding the variables idle agreed and idle sleeping, were not observed effects of substitution levels of SM by DCC. The DCC provides no changes in the behavior of the sheep, but the period of the day exerts influence on the behavioral pattern of such animals.